OSING YOUTH’S INVOLVEMENT IN PRESERVING LOCAL WISDOM THROUGH THE GANDRUNG SEWU FESTIVAL - Francisca Titing Koerniawaty; Komang Artana; I Made Yuda Adnyana; I Putu Mega Adi Adnyana; Gusti Ngurah Indra Ariestyawan; Risky Maulana; Anedda Alessandro Flavio Putra (Journal of Innovation Research and Knowledge, 2025)
This study examines the strategic involvement of Osing youth in preserving local culture through their participation in the Gandrung Sewu Festival in Banyuwangi. This annual festival functions not only as an artistic performance but also as a medium for transmitting Osing cultural values and promoting culture-based tourism. Employing a descriptive qualitative approach framed by theories of social participation, cultural transmission, cultural tourism, and cultural festivals as preservation and promotion tools. The research explores various forms of youth involvement, ranging from dancers, organizing committees, and art facilitators to digital promoters. The findings reveal that youth participation is predominantly symbolic, although creative initiatives have emerged, such as the Gandrung Anak Muda community, which utilizes social media and digital content innovation. Key driving factors include cultural identity and community support, while challenges consist of limited training, inadequate cultural facilities, and the influence of popular culture. The study underscores the importance of engaging young generations in all stages of sustainable cultural preservation. The Gandrung Sewu Festival holds significant potential as an educational platform and as a driver of culture-based creative economy. Recommendations are directed toward strengthening digital strategies, fostering early cultural education, and implementing participatory cross-generational policies